BRAF V600E and Pten deletion in mice produces a histiocytic disorder with features of Langerhans cell histiocytosis. - David S Nelson; Ryan L Marano; Yechaan Joo; Sara Y Tian; Bhumi Patel; Daniel H Kaplan; Mark J Shlomchik; Kristen Stevenson; Roderick T Bronson; Barrett J Rollins (PLoS ONE)
Langerhans cell histiocytosis (LCH) is characterized by the accumulation of Langerin (CD207)-expressing histiocytes. Mutational activation of mitogen-activated protein kinase pathway genes, in particular BRAF, drives most cases. To test whether activated BRAF is sufficient for the development of LCH, we engineered mice to express BRAF V600E under the control of the human Langerin promoter. These mice have shortened survivals, smaller lymphoid organs, absent Leydig cells, and fewer epidermal LCs than controls, but do not accumulate histiocytes. To test whether the absence of histiocyte proliferation could be due to oncogene-induced senescence, we engineered homozygous Pten loss in the same cells that expressed BRAF V600E. Like mice with intact Pten, these mice have shortened survivals, smaller thymi, and absent Leydig cells. However, loss of Pten also leads to the accumulation of CD207+ histiocytes in spleen, thymus, and some lymph nodes. While many CD207+ histiocytes in the thymus are CD8-, reminiscent of LCH cells, the CD207+ histiocytes in the spleen and lymph nodes are CD8+. These mice also accumulate large numbers of CD207- cells in the lamina propria (LP) of the small intestine. Both the lymphoid and LP phenotypes are likely due to human Langerin promoter-driven BRAF V600E expression in resident CD8+ dendritic cells in the former and LP dendritic cells in the latter and confirm that Pten loss is required to overcome inhibitory pathways induced by BRAF V600E expression. The complex phenotype of these mice is a consequence of the multiple murine cell types in which the human Langerin promoter is active.